Host Immunity Influences the Composition of Murine Gut Microbiota - Van averbeke, Vincent; Berkell, Matilda; Mysara, Mohamed; Rodriguez-Ruiz, Juan Pablo; Xavier, Basil Britto; De Winter, Fien H. R.; Jongers, Bart ‘s; Jairam, Ravi Kumar; Hotterbeekx, An; Goossens, Herman; Cohen, E. Suzanne; Malhotra-Kumar, Surbhi; et al. (Frontiers in Immunology, 2022)
The gut microbiota influences several aspects of immunity, and its disturbance is linked to several immune-mediated disorders. While the influence of gut microbiota on host immunity is widely studied, conversely, whether and how inherently disturbed canonical Th1 (proinflammatory) and/or Th2 (anti-inflammatory) immune pathways modify the host microbiome is not sufficiently investigated. We first showed here that wild type mice (C57BL/6 and BALB/c), but not mice lacking Th2 (IL-4Rα and IL-33 knockout mice) or both Th1 and Th2 responses (NOD scid gamma mice), are enriched in gut bacteria that produce short-chain fatty acids and are commonly considered probiotics. Examples of these probiotic bacteria are members of phyla Firmicutes, Verrucomicrobia, and Bacteroidetes that includes Lactobacillus, Akkermansia muciniphila, and Odoribacter spp. Utilizing T-cell and blood cytokine analyses of naïve wild type mice, we further showed that C57BL/6 lean towards Th1 polarization compared to BALB/c mice, and this subtle immune alteration is already strongly linked to alterations in gut microbial composition. These data demonstrate the direct influence of host immunity in regulating the gut microbiota. Moreover, as the murine and human immune system as well as dominant bacterial taxa in the gut show a remarkable similarity, we believe that the microbial alterations identified in this study will be highly relevant for the understanding of microbial alterations in human immunodeficient disorders.